Stop the Bleed: gap analysis and geographical evaluation of incident locations. Issue 1 (18th February 2020) - Tsui, Michelle; Carroll, Shannon L.; Dye, Daniel W.; Smedley, W. Andrew; Gilbert, Aidan D.; Griffin, Russell L.; McGwin, Gerald; Stephens, Shannon W.; Kerby, Jeffrey D.; Jansen, Jan O.
Abstract : Background: Trauma is a major public health issue. In 2015, the White House launched the "Stop the Bleed" (STB) campaign, which aims to equip would-be bystanders with the ability and equipment to assist in bleeding emergencies. This study sought to estimate the number of patients who might benefit from STB intervention, in an everyday setting, and their spatial injury profile. Methods: This is a retrospective analysis of trauma registry and medical examiners' data, collected between 2013 and 2017. The majority of patients were male. The median age was 32 years. Incidents were geocoded by ZIP code, and mapped using Quantum Geographic Information System (QGIS). Results: We identified 139 patients from medical examiner records and UAB's trauma registry who might have benefitted from STB intervention. The number of incidents per year ranged from 22 to 35, averaging 2.3 incidents per month. There was no evidence of geographical clustering, although the small number of incidents precluded a formal geostatistical analysis. Conclusion: The number of patients who might benefit from STB interventions on a daily basis is small, and incident locations are difficult to predict. Educating the public in how to stop bleeding is appealing, but providing easy and widespread access to STB kits may be difficult. Although there are parallels to the provision of cardiopulmonary resuscitation and defibrillation for cardiac arrest, there are also differences, which should not be overlooked.